2015
DOI: 10.1155/2015/714158
|View full text |Cite
|
Sign up to set email alerts
|

Sauropus androgynus(L.) Merr. Induced Bronchiolitis Obliterans: From Botanical Studies to Toxicology

Abstract: Sauropus androgynus L. Merr. is one of the most popular herbs in South Asia, Southeast Asia, and China where it was known as a slimming agent until two outbreaks of pulmonary dysfunction were reported in Taiwan and Japan in 1995 and 2005, respectively. Several studies described that the excessive consumption of Sauropus androgynus could cause drowsiness, constipation, and bronchiolitis obliterans and may lead to respiratory failure. Interestingly, this herb has been used in Malaysia and Indonesia in cooking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
0
42
0
3
Order By: Relevance
“…Interestingly, supplementation of sunflower seeds or sunflower oil had a positive effect on milk yield and milk composition in lactating goats (Morsy et al, 2015). Although having an association with bronchiolitis (Sawahata et al, 2010) and cytotoxic activity (Yunita et al, 2013), Sauropus androgynus is traditionally consumed by several Southeast Asian countries and is believed to be an enhancer of milk production during lactation (Bunawan et al, 2015). When feeding S. androgynus leaf extract to lactating mice, it enhanced the expression of two prominent genes (prolactin and oxytocin) regulating milk production and subsequently, increased milk production (Soka et al, 2010) suggesting their potential use to increase milk production in livestock ruminants (Gabbi et al, 2015).…”
Section: Milk Productionmentioning
confidence: 99%
“…Interestingly, supplementation of sunflower seeds or sunflower oil had a positive effect on milk yield and milk composition in lactating goats (Morsy et al, 2015). Although having an association with bronchiolitis (Sawahata et al, 2010) and cytotoxic activity (Yunita et al, 2013), Sauropus androgynus is traditionally consumed by several Southeast Asian countries and is believed to be an enhancer of milk production during lactation (Bunawan et al, 2015). When feeding S. androgynus leaf extract to lactating mice, it enhanced the expression of two prominent genes (prolactin and oxytocin) regulating milk production and subsequently, increased milk production (Soka et al, 2010) suggesting their potential use to increase milk production in livestock ruminants (Gabbi et al, 2015).…”
Section: Milk Productionmentioning
confidence: 99%
“…Besides some were imported from abroad, S. androgynus consumed in Taiwan market were mostly cultivated species. Recent phytochemical studies described that the plant contains a wide range of biomolecules constituents that might contribute to its medicinal, toxic, and antioxidant properties [6]. A hospital-based case-control study of 54 victims observed that an excessive intake, uncooked regimen, and consuming vendor's preparation were the risk factors of the event [7].…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin and luteolin are flavonoids found in S. androgynus which have been proven to prevent inflammation caused by Salmonella infection in mice. 13 The administration of katuk leaves to PE goats also increases the concentration of testosterone.…”
Section: Sauropus Androgynousmentioning
confidence: 99%